Primary spinal melanoma of extramedullary origin: a report of three cases and systematic review of the literature - Liu, Q-Y (Spinal Cord Ser Cases, 2015)
STUDY DESIGN: A review of the literature and three case reports. OBJECTIVES: Primary spinal melanoma (PSM) of extramedullary origin is a rare malignant condition with limited current literature in regards to its clinical course, magnetic resonance imaging (MRI) findings, treatment strategies and prognosis. We reported here three cases of PSM of extramedullary origin. SETTING: China, Guangzhou. METHODS: We report three cases of PSM of extramedullary origin. The clinical and radiological findings of these cases were retrospectively analyzed. RESULTS: The three cases were all of males aged 39, 47 and 76 years, respectively. The duration of their symptoms was 3 weeks, 2 months and 11 months respectively. The extramedullary tumors were all well-defined solitary tumors and were located at C4-5, L2-3 and T9-10, respectively. In one case, involvement of the intervertebral foramen was found. Preoperative MRI showed hyperintense T1W signals and hypointense T2W signals in all three cases and all tumors were clinically misdiagnosed as schwannomas. The patients received total or subtotal resection surgery without radiotherapy or chemotherapy. Patients were alive at 18 months, 27 months and 36 months postoperative follow-up, respectively. CONCLUSION: PSM of extramedullary origin is a rare malignant tumor that shows characteristic findings on MRI. Surgical resection is the preferred treatment strategy.